Association between insomnia severity and presenteeism among Japanese daytime workers. (25th August 2022) - Takano, Yuta; Ibata, Rui; Nakano, Norihito; Sakano, Yuji
Summary: Presenteeism is the loss of productivity due to a worker's health problems, despite the worker being present at the workplace. Although the association between presenteeism and insomnia complaints is well known, few studies have examined the association between insomnia severity and presenteeism. This study aimed to explore the association between insomnia severity and presenteeism. This study included 1925 participants (1543 males, 379 females, and three of other genders) in total. The mean age of the participants was 49.94 ± 9.82 years. The inclusion criteria were full‐time employment, working 8 hr per day and 5 days per week, and having no night shifts. The insomnia severity was classified based on the Insomnia Severity Index and Athens Insomnia Scale criteria. Logistic regression analysis showed that moderate and severe insomnia severity were associated to a greater magnitude with presenteeism than mild insomnia severity. Severe insomnia severity was associated to a greater magnitude with presenteeism than moderate insomnia severity. In summary, logistic regression analysis showed that increased insomnia severity based on Insomnia Severity Index classification was associated with increased odds of presenteeism, but increased insomnia severity based on Athens Insomnia Scale classification was not fully consistent with increased odds of presenteeism. Because increased insomnia severity is associated with worsening of presenteeism, early detection of and early intervention against insomnia complaints are important for reducing presenteeism. This study was the first to examine the associations between presenteeism and insomnia severity classification of no insomnia, mild, moderate, and severe insomnia severity.